Structural elucidation of coreâshell TiO2 nanomaterials for environmental pollutants removal: A focused mini review - Nawaz, R. (Elsevier B.V., 2020)
Recently, coreâshell structured titania (CS TiO2) nanomaterials has garnered enormous research interest due to its improved visible light absorption capability and performance for various applications. While CS TiO2 nanomaterials have shown satisfactory performance in other applications, its solar light photocatalytic performance is still far from excellent for environmental pollutants removal. This might be due to the poor understanding of mismatch between the various structural properties of CS TiO2 and the contaminant we target for or scarcity of information about the atomic, nanocrystalline and electronic structure of CS TiO2 and its correlation with photocatalytic performance. The present review provides an in-depth understanding of propertyâperformanceâ relationship, specifically for the removal of organic pollutants from environmental media, which will help further understand and optimize the photocatalytic properties of CS TiO2 for enhancing its solar driven photocatalytic activity. The formation mechanism, structural properties, and photocatalytic performance of CS TiO2 for environmental pollutants removal were reviewed, and it is established that an inclusive strategy is needed to address the key challenges in designing CS TiO2 for environmental pollutants removal. The key challenges are the management of the location and concentration of defects states, optimization of surface to bulk defects ratio, and controlling the thickness of the shell. Conclusive prospective research needs for tuning the nanocrystalline structure and associated properties of CS TiO2 are suggested accordingly. Â© 2020 Elsevier B.V.